Maqamat sufi untuk menuju Tuhan dan perbedaan dengan Hal - Muslikh, Muhammad Rifqi Baidlowi (Maliki Interdisciplinary Journal, 2025)
This articel the concept of maqamat in Sufism, which refers to the spiritual stages that a Sufi must pass through to draw closer to Allah SWT. Maqamat derives from the Arabic word maqam, meaning rank or status, and in the context of Sufism, it reflects human efforts to attain specific spiritual positions through spiritual exercises, worship, and mujahadah (striving). Each maqam requires consistent effort and the enhancement of spiritual quality, involving specific practices until one is capable of progressing to the next stage.The discussion includes the definition of maqamat, types of maqamat such as repentance (taubah), asceticism (zuhud), patience (sabr), trust (tawakkul), and contentment (rida), as well as differing views among Sufi scholars regarding the number of these stages. The paper also elaborates on the relationship between maqamat and ahwal (spiritual states), where ahwal function as divine blessings that support a Sufi’s journey toward higher stages. Using a descriptive approach, this paper provides an in-depth understanding of the significance of maqamat in shaping a Muslim’s character and spirituality and how this journey leads to total surrender to Allah SWT.